(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article is devoted to the analysis of organizational culture. Under the conditions of economic modernization, current scientific publications on theories and models of organizational culture were studied to determine ways of analyzing and developing organizational culture in companies. The study of organizational culture made it possible to gain a deeper understanding of how organizations function internally and adapt to changing external environments. The article begins with an analysis of empirical patterns observed in organizational cultures around the world and presents general conclusions about their manifestation in companies in Uzbekistan.